2018
DOI: 10.1021/acssuschemeng.8b01124
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Detection of Formaldehyde in Gas and Solutions by a Catalyst Preplaced Sensor Based on a Pillar[5]arene Derivative

Abstract: Abnormal formaldehyde (FA) is known to induce a variety of diseases. Herein, we report a novel and efficient method for ultrasensitive detection of formaldehyde in gas and solutions by a catalyst preplaced sensor based on the pillar[5]­arene derivative (DP5J). By the catalyzation of (CF3SO3)2Bi, DP5J could selectively and sensitively sense formaldehyde through an aggregation-induced emission (AIE) “turn-on” response within 7.5 s, and the detection limits for formaldehyde is 3.27 × 10–9 M. Moreover, a FA test k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…The intensity of the fluorescence centered at 464 nm decreases when increasing concentration of aniline, the calibration curve of COFÀ PyÀ AN for aniline showed the better linearity between 0.04 to 0.34 mM (Figure 3a, Figure S11). The limit of detection [48] of COFÀ PyÀ AN toward aniline was 1.29 μM. Compared with other similar methods (Table S2), the COF material has a relatively low detection limit, indicating that COFÀ PyÀ AN has good sensitivity.…”
Section: Fluorescence Propertymentioning
confidence: 86%
“…The intensity of the fluorescence centered at 464 nm decreases when increasing concentration of aniline, the calibration curve of COFÀ PyÀ AN for aniline showed the better linearity between 0.04 to 0.34 mM (Figure 3a, Figure S11). The limit of detection [48] of COFÀ PyÀ AN toward aniline was 1.29 μM. Compared with other similar methods (Table S2), the COF material has a relatively low detection limit, indicating that COFÀ PyÀ AN has good sensitivity.…”
Section: Fluorescence Propertymentioning
confidence: 86%
“…Compared to naked-eye-visual colorimetric methods, fluorometric chemosensors exhibit relatively rapid response and high sensitivity for detection of trace gaseous analytes under UV light irradiation. 34,60,96,97 According to fluorometric chemosensors for detecting aldehydes, this paper divided the reaction mechanism into four categories, including aldimine condensation, [98][99][100][101][102][103][104][105] Aza-Cope rearrangement, [106][107][108][109] QDs adjustment, 110,111 and functional MOFs interaction. 112,113 Most of these reactive fluorescent probes have been applied to detect aldehydes through the chemical reaction between -CHO group and the amine group on the probe.…”
Section: Fluorometric Sensorsmentioning
confidence: 99%
“…In addition, the unique molecular structure of pillar[n]arenes leads to various supramolecular assembly driving forces, including C-H-π, π-π, cation-π, hydrophobic/hydrophilic, etc., which provides a novel platform for the construction of various interesting supramolecular systems, as well as AIE-based chemosensors. [118][119][120][121] An AIE-based sensor 105 with LDL of 0.1 ppb towards FA in 7.5 s was developed by introducing the hydrazide groups into pillar [5]arene (DP5J) (Fig. 19a).…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…This work was published in 2018, which indicates that the preparation of supported sensors for formaldehyde is a hot research area. Also in 2018, Wei et al reported a formaldehyde sensor based on the aggregation-induced emission (AIE) effect [ 34 ]. In this case, the probe contained a complex structure and needed bismuth salts to detect the analyte.…”
Section: Introductionmentioning
confidence: 99%